2006
DOI: 10.1007/s11418-006-0035-5
|View full text |Cite
|
Sign up to set email alerts
|

Preventive and curative effects of curcumin on the development of gastric inflammatory diseases in rats

Abstract: Preventive and curative effects of curcumin on experimental acute and chronic gastric ulcers were investigated to validate its clinical application on a remedy for peptic ulcer. Intraduodenal administration of curcumin, 5-20 mg/kg, inhibited gastric acid secretion in pylorus-ligated rats, and oral administration prevented ethanol-induced acute gastric mucosal lesions. Curcumin (20-80 mg/kg, p.o.) dose-dependently prevented both serotonin-induced gastric mucosal lesions and compound 48/80-induced gastric mucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…An oral dose of curcumin at 20–80 mg/kg twice daily has been reported in the treatment of gastric ulcers in rats [ 38 ], whereas no exact dosage has been reported for humans. Although the developed sponge systems in this study contained a relatively low drug content of 3 mg/capsule, the amount of curcumin released was approximately 10 times greater compared to the plain curcumin, as shown in Figure 8 .…”
Section: Resultsmentioning
confidence: 99%
“…An oral dose of curcumin at 20–80 mg/kg twice daily has been reported in the treatment of gastric ulcers in rats [ 38 ], whereas no exact dosage has been reported for humans. Although the developed sponge systems in this study contained a relatively low drug content of 3 mg/capsule, the amount of curcumin released was approximately 10 times greater compared to the plain curcumin, as shown in Figure 8 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, curcumin acts as gastroprotectant against irritants by increasing mucin secretion in rabbits. It also decreases indomethacin induced increment in the luminal acid level, which is beneficial to prevent acid-induced aggravation of ulcer by its potent antioxidant activity through scavenging of reactive oxygen species (ROS) and protection of gastric peroxidase [75].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that it exhibits anti-infection properties (8) and has the ability to inhibit inflammatory cell proliferation, invasion, and angiogenesis, through numerous molecular targets and mechanisms of action (18,19). Curcumin has been shown to reduce gastric acid production and concentration (20). WRS has been reported to produce band-like hemorrhagic lesions in the glandular portion of the stomach (21).…”
Section: Discussionmentioning
confidence: 99%